2007
DOI: 10.1007/s00359-007-0307-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between descending input and thoracic reflexes for joint coordination in cockroach: I. Descending influence on thoracic sensory reflexes

Abstract: Tethered cockroaches turn from unilateral antennal contact using asymmetrical movements of mesothoracic (T2) legs (Mu and Ritzmann in J Comp Physiol A 191:1037-1054, 2005). During the turn, the leg on the inside of the turn (the inside T2 leg) has distinctly different motor patterns from those in straight walking. One possible neural mechanism for the transformation from walking to inside leg turning could be that the descending commands alter a few critical reflexes that start a cascade of physical changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 42 publications
4
36
0
1
Order By: Relevance
“…In this case and in the case of the reduced variability in the inside leg stepping pattern, it is not clear in which way this shaping effect of the motor output by sensory signals may occur. The notion, however, that shaping of one general motor pattern such as the straight/outside pattern into two more refined ones may be mediated by the action of descending signals is supported by recent findings in the cockroach where it was shown that a reflex response that is involved in the execution of searching/inside leg turning is altered after removal of descending input from the brain (Mu and Ritzmann, 2008a). One word of caution should be added about the interpretation of the reduced variability in the stepping kinematics of the inside middle leg.…”
Section: Straight Walking and Turning In The Reduced Preparationmentioning
confidence: 92%
“…In this case and in the case of the reduced variability in the inside leg stepping pattern, it is not clear in which way this shaping effect of the motor output by sensory signals may occur. The notion, however, that shaping of one general motor pattern such as the straight/outside pattern into two more refined ones may be mediated by the action of descending signals is supported by recent findings in the cockroach where it was shown that a reflex response that is involved in the execution of searching/inside leg turning is altered after removal of descending input from the brain (Mu and Ritzmann, 2008a). One word of caution should be added about the interpretation of the reduced variability in the stepping kinematics of the inside middle leg.…”
Section: Straight Walking and Turning In The Reduced Preparationmentioning
confidence: 92%
“…Indeed, it has been suggested that reflex modification is not simply a corollary of switching locomotor patterns, but is the essence of the switch. For example, in a walking insect, a command to turn may consist simply of the modification of leg mechanosensory reflexes such that turning is the natural result [187, 188]. …”
Section: From Mechanosensation To Action: the Problems Faced By The Cmentioning
confidence: 99%
“…For example, in the cockroach, removing the descending projections from the brain alters certain mechanosensory reflexes [187]. A recent study extended this finding to show that electrical stimulation of neurons in the cockroach central complex can alter the tibial resistance reflex [192].…”
Section: From Mechanosensation To Action: the Problems Faced By The Cmentioning
confidence: 99%
“…During turning and backward walking movements, the signs of these reflexes can change resulting in altered joint coordination in specific legs (Akay et al, 2007;Hellekes et al, 2012). In cockroaches, elimination of descending activity through bilateral lesion of cervical connectives can reverse the local chordontonal organ reflexes (Mu and Ritzmann, 2008a). Taken together, these studies suggest that descending commands from the brain can alter leg coordination by changing a few crucial reflexes that start a cascade of changes in leg movements or posture (Mu and Ritzmann, 2008b), which in turn could lead to the transition from straight walking to turning.…”
Section: Interactions With Thoracic Neuronsmentioning
confidence: 99%